Development of evolutionary search algorithms with binary choice relations when making decisions for pellet tubular heaters - Irodov, Vyacheslav; Shaptala, Maksym; Dudkin, Kostiantyn; Shaptala, Daria; Prokofieva, Halyna (Eastern-European Journal of Enterprise Technologies, 2021)
A study was carried out and the optimization process was carried out for one of the types of equipment for autonomous heat supply using renewable resources – a tubular pellet heater. The research is expedient, since there is no mathematical model of the unit operation for the pellet combustion unit, there is only a set of experimental results indicating the inconsistency of the criteria presented to it. As a result of the research, new algorithms have been obtained: firstly, an algorithm for selecting (multi-criteria optimization) the operating mode of the unit for burning pellets of tubular heaters, and secondly, algorithms for choosing, according to several criteria, the parameters of the heat exchange unit of a tubular heater with a screen. A set of algorithms for multicriteria optimization with binary selection ratios has been developed for tubular pellet heaters in full, including a pellet combustion unit and a heat exchange unit. Selection functions have been defined for a pellet combustion unit using dimensionless complexes based on experimental results. For a block of a tubular heat exchanger with a screen, a selection function is built taking into account the criteria of functioning and a mathematical model of the heater in the form of a system of nonlinear ordinary differential equations. The practical significance of the algorithm for selecting the operating mode for the pellet combustion unit lies in the possibility of obtaining the most preferable (optimal, taking into account many criteria) parameters in the entire range of permissible parameters, and not only among the experiments carried out. The practical significance of optimization algorithms for a heat exchange unit lies in the ability to select specific parameter values during design – the thermal power of the heater, air flow, the length of the tubular part and the screen, their diameters, taking into account several selection criteria.